TRIZ method for innovation applied to an hoverboard. Issue 1 (1st January 2018) - Donnici, Giampiero; Frizziero, Leonardo; Francia, Daniela; Liverani, Alfredo; Caligiana, Gianni
Abstract: The aim of this work is to complete the QFD analysis carried out in a previous work that aimed to identify the main features that contribute to the success of a modern urban transport means: the hoverboard. Starting from this analysis, through the TRIZ methodology, resolutive principles have been identified for the realization of innovative solutions of the said urban transport means. In practice this analysis aims to manage the next phase of conceptual design realized with the QFD methodology and tries to guide the design process in its next phase. In this work was used the hill model, a characteristic model of the TRIZ methodology, and the technical innovative problems encountered were reformulated in terms of technical contradictions. Subsequently, general principles of inventive solutions were obtained using one of the tools of TRIZ: the matrix of contradiction. Finally, starting from these general principles of solution, innovative constructive solutions have been developed to be applied to the design of an innovative hoverboard.